Tailored platinum-nickel nanostructures on zirconia developed by metal casting, internal oxidation and dealloying. (November 2016) - Terock, M.; Konrad, C.H.; Popp, R.; Völkl, R.; Yang, F.; McComb, D.W.; Mills, M.J.; Glatzel, U.
Highlights: Hierarchical structure of pores adjustable by metallurgical means. Homogenous distribution of nanostructured Pt-Ni onto the surface of highly porous zirconia support. Initial alloys can be created by a variety of normal metal processing procedures. Flexible new process for manufacturing catalysts, electrodes and sensors. Abstract: Noble-metal nanostructures are crucial, highly active materials in applications such as fuel cells, sensors, electrodes and catalysts. The present work shows a new and efficient method for the in-situ synthesis of platinum-nickel nanostructures on porous zirconia. Ni-Zr-Y metallic alloys with defined Zr/Y-ratios and small amounts of platinum are internally oxidized. An interpenetrating network of yttria-stabilized zirconia (YSZ) in pure nickel is formed. Dealloying of the nickel matrix generates a multimodal porous ceramic support structure with platinum-nickel nanostructures on the surface of the zirconia-ceramic with a broad spectrum for tailored functionality, for example in after-treatment of exhaust gases.